Correction to: Risk-reducing salpingo-oophorectomy, natural menopause, and breast cancer risk: an international prospective cohort of BRCA1 and BRCA2 mutation carriers - Mavaddat, Nasim; Antoniou, Antonis C; Mooij, Thea M; Hooning, Maartje J; Heemskerk-Gerritsen, Bernadette A; Noguès, Catherine; Gauthier-Villars, Marion; Caron, Olivier; Gesta, Paul; Pujol, Pascal; Lortholary, Alain; Barrowdale, Daniel; et al. (Breast cancer research, 2020)
After publication of the original article [1], we were notified that columns in Table 2 were erroneously displayed.